One Line Plus Soft Keyboard Layout for Smartwatches Text Entry - Eka Prakarsa Mandyartha; Fawwaz Ali Akbar; Auliya Arkhan (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The "One Line Plus" soft keyboard layout inspired by One Line and T9 layouts. This innovative design condenses the button layout into a single line, maximizing button size for ease of use. The implementation includes essential features like enter and autocorrect buttons to enhance user experience. Performance testing involving 31 participants was conducted to evaluate the effectiveness of the layout. The results showed an average words per minute (WPM) of 8.8 and a total character count of 43.48, with the highest WPM of 16 and character count of 89, and the lowest WPM of 4 and character count of 16. The analysis grouped participants based on their background, experience with smartwatches, and typing intensity. Notably, the group with frequent typing experience on smartwatches achieved the highest WPM of 11.3 and character count of 53.4, indicating the layout's efficacy for proficient users. The System Usability Scale (SUS) evaluation yielded an average score of 89.35, indicating the layout's successful usability. These findings demonstrate the potential of the One Line Plus soft keyboard layout for enhancing text entry on smartwatches.